ANALYSIS OF DESIGN STRATEGY IMPLEMENTATION OF HUMAN RESOURCES IN BIOFLOC SYSTEM FISH LIVESTOCK BUSINESS UNIT AT MUAMALAT NAHDLATUL ULAMA SYARIAH COOPERATIVE KASOMALANG - Mutqi Sopiawadi (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2022)
This research aims to form and develop human resources in a new unit of analysis, namely the Muamalat Nahdatul Ulama Sharia Cooperative. The type of research conducted is descriptive qualitative in this study only in the form of descriptions and statements regarding employee performance using a saturated sampling technique where the saturated sample is a census, where all cooperative members are sampled. The data sources used in this study used primary data obtained from results of interviews, documentation and literature studies as well as secondary data in this study in the form of data obtained from libraries,journals and articles. In this study it was determined that activities suitable for the Muamalat Nahdlatul Ulama Sharia Cooperative in improving the skills and quality of human resources by carrying out training activities for each employee who manages cultivation activities using the biofloc system so as to produce employees who have high knowledge of the cultivation of the biofloc system . As well as in increasing the effectiveness, efficiency and productivity of employees can be carried out routine evaluation activities as well as providing rewards and punishments for each employee.